PENGARUH AFFILIATE MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FLORAL.ID OFFICIAL DI TIKTOKSHOP (Study Pada Gen Z yang merupakan Followers Tiktok Floral.id Official di Desa Pangaur Kecamatan Jasinga) - Karina Putri Utami; Mahnun Mas’adi (LAP4B, 2026)
This study aims to examine the influence of Affiliate Marketing and Product Quality on Purchase Decisions of Floral.id Official products on TikTok Shop (A Study on Generation Z followers of the TikTok account Floral.id Official in Pangaur Village, Jasinga District). The research employs a quantitative approach using an associative research method. A total of 96 respondents were selected through purposive sampling. The results of the t-test show that Affiliate Marketing (X1) has a positive and significant influence on Purchase Decision (Y), with a t-value of 5.945 > t-table 1.985 and a significance level of 0.000 < 0.05. Likewise, Product Quality (X2) also has a positive and significant effect, indicated by a t-value of 7.970 > t-table 1.985 and a significance level of 0.000 < 0.05. The F-test results further support these findings, showing an F-value of 41.833 > F-table 3.09 with a significance level of 0.000 < 0.05. In other words, both Affiliate Marketing and Product Quality simultaneously have a significant impact on Purchase Decision. This study confirms that consistent affiliate marketing and high product quality can drive Generation Z’s purchase decisions toward Floral.id products on TikTok Shop. Therefore, it is recommended that the company strengthen its collaboration with affiliates who align with the target market and maintain product quality to remain relevant to Gen Z consumers in the digital era.